Volume 2D: Turbomachinery 2017
DOI: 10.1115/gt2017-63400
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Behavior of Diffuser Stall in a Centrifugal Compressor With Vaned Diffuser

Abstract: In this study, the unsteady behavior of a diffuser rotating stall in a centrifugal compressor with a vaned diffuser was investigated through experiments and numerical analyses. From the casing static pressure measurements, it was determined that the diffuser stall propagated at 25% of impeller rotational speed in the vaneless space. The numerical results revealed the presence of a typical vortical structure on the diffuser’s leading edge. Under partial flow condition, a tornado-type vortex was generated on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…As Eck et al accurately pointed out, the rotating instability cells are induced by the small vortices propagating at the rotor leading edge [11]. We have also reported that the unsteady behavior of the diffuser stall is influenced by the unsteady vortices at the leading edge of the diffuser vane, during off-design operation [12]. Especially, we demonstrated that the diffuser stall cell is caused by the systematic vortical structure, which consisted of a tornado-type vortex, LEV, and a vortex in the throat area of the diffuser passages, as described in Fig.…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations
“…As Eck et al accurately pointed out, the rotating instability cells are induced by the small vortices propagating at the rotor leading edge [11]. We have also reported that the unsteady behavior of the diffuser stall is influenced by the unsteady vortices at the leading edge of the diffuser vane, during off-design operation [12]. Especially, we demonstrated that the diffuser stall cell is caused by the systematic vortical structure, which consisted of a tornado-type vortex, LEV, and a vortex in the throat area of the diffuser passages, as described in Fig.…”
Section: Introductionmentioning
confidence: 51%
“…The present simulations were conducted using an in-house computational fluid dynamics (CFD) code, which had been validated for various turbomachinery flows [12,18,19] [20], which was extended to the third order using the monotonic upwind scheme for conservative laws (MUSCL) interpolation [21]. The viscous flux was determined as a second-order central difference by using Gauss's theorem.…”
Section: Computational Procedures Governing Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide stable operating range of vaned diffusers is therefore important to meet these requirements. Fujisawa et al [4] and Fujisawa et al [5] studied the diffuser stall mechanism in an open impeller centrifugal compressor stage with a wedge diffuser. As initiation for diffuser instability a rotating diffuser stall was observed on shroud side.…”
Section: Introductionmentioning
confidence: 99%